How to do archaeology the right way - Purdy, Barbara A. (University Press of Florida, 1996)
Despite field conditions that often include bug bites, bad food, and nonexistent plumbing, legions of amateur archaeologists regularly take to the field - sometimes a muddy one - to dig up ceramic pots, animal bones, and stone spearheads. This book explains how and why the professionals do it. In nontechnical language directed at the general public, conservation groups, and land developers, Barbara Purdy summarizes the prehistory of Florida and describes how responsible archaeologists excavate and analyze remains. She answers the questions "How do archaeologists know where to dig?" and "Why do they excavate a particular site?" and discusses the months of planning, surveying, mapping, testing, fund raising, and permit acquisition that precede an excavation. She also includes information on the rules and regulations governing digs, on artifact analysis, dating, and preservation, and on the ways in which excavation affects the balance of nature